Computation of Climatic Water Balance for Greater Musaiyab Project Site in Babylon Governorate- Central of Iraq - A. Al-Dabbas , Moutaz; AL-Ali, Eman A. (Iraqi Journal of Science, 2022)
The meteorological data recorded in Al-Hilla station for the period (1984-2014) were used to describe the climatic condition of the Greater Musaiyab Project lies in Babylon Governorate, 90Km southern of Baghdad City, central of Iraq. This study found that the summation of rainfall is (112.323 mm), average of relative humidity (47.44%), temperature (25.55 C◦), sunshine (8.748 h/day) and the total of evaporation is (2268.463 mm). In this research, three classifications were applied to find the type of climate in the study area. The results of the climate classification show that, the climate of study area is characterized by dry and relatively hot in summer, and cold with low rain in winter. Thornthwiat equation was used to determine the values of the potential evapotranspiration. This study shows that, there is water surplus of (39.12 %) of the total rainfall amount which is equivalent to (112.323 mm).